An Annual and Seasonal Characterisation of Winery Effluent in South Africa - Sheridan, C.M.; Glasser, D.; Hildebrandt, D.; Petersen, J.; Rohwer, J. (South African Journal of Enology and Viticulture, 2016)
Winery effluent is known to have a high chemical oxygen demand (COD) and a low pH. In this study, we extensively analysed effluent from two cellars and studied the temporal changes over the duration of a harvest and the duration of a year. We found that ethanol contributes approximately 85% to 90% of the COD of raw winery effluent, with acetic acid being the next significant contributor. The pH showed some dependence on the concentration of acetic acid. The concentration of sodium in the effluent is strongly dependent on the cleaning regime in place at the cellar, and the concentration of potassium has been shown to be linked to the spillage of juice, wine or lees. The data and correlations presented here could allow for an artificial effluent to be prepared easily for research purposes.